Penerapan maklumat variasi nasional dalam kamus Melayu-Indonesia (Jurnal Bahasa, 2006)
This research is a comparative study that discusses the scenario of Malay and Indonesian dictionaries from the lexical aspect. It is based on the analyses of Kamus Dewan, Fourth Edition (2005) (henceforth, KD), Kamus Besar Bahasa Indonesia, Third Edition (2001) (hence-forth KBBI), Kamus Melayu Global (1996), Kamus Umum Bahasa Indonesia Badudu-Zain (1994) and Kamus Bahasa Melayu R.O. Winstedt (1960). This study focuses on the national variation informa-tion treatment. The researcher found that all the dictionaries did not have balanced treatment of the information concerning the lexical as-pect of the home variety and the away variety of the Malay language. Suggestions have been put forward that serve as valuable inputs for the development of the Malay-Indonesian lexicographic world.